Cultura de paz e inclusão escolar: sentidos da política humanizadora no trabalho das professoras do atendimento educacional especializado (AEE) da rede pública municipal de Fortaleza - Viegas, Ana Patrícia da Silva Mendes Paton (2018)
This study aims to analyze how the culture of peace has been promoted, from the inclusive labor political meaning understanding of seven teachers who work in the special educational service in public schools in the Municipal System in Fortaleza. In a specific way, the research sought to identify the political dimension that the teachers attach to work with the educational community, and to analyze the established relation between the inclusive labor policy meanings and the positive peace and productive conflict concepts. The research begins with the perception that the interlocution between the culture of peace and inclusion, through dialogic, promotes the autonomy development, like act of resistance, deconstructing the peace concept as passivity, towards the structural violence at schools. A qualitative approach with collected data was used through the focus group with seven teachers, who work in the special educational service on the locus in the formation of the Education II district in the Municipal Department of Education in Fortaleza, besides the data records in field diary, bibliographic and documental researches. It was done a participant observation, an on-line questionnaire and the focal group involvement to work with the teachers. The data analyzes was based into four theme pre-defined categories, such as inclusion political meanings, dialogic, positive peace and productive conflict. The theoretical principles were based on well-known authors like Freire (1970,1979, 1987, 2005), Matos (2001, 2002, 2006), Jares (2002, 2006, 2007), Guimarães (2011), Perrenoud (2001), Mantoan (2006,2010), among others, and it was found out that the teachers grant two political meanings to the AEE work. The first one is seen as a legal rule reflection shown in the laws formality and in the traditional politics. The latter meaning points out the daily inter-subjective relations. It was also found out that the political meaning granted to the inter-subjective relations contributes to the respect for differences, the search for partnerships (teachers who work in related areas, public administrators, multidisciplinary team, families, and methods), the problematization about the reality of the community, the search for the inclusion commitment and the genesis of conflicts understanding and its mediation. Everything is connected to positive peace and to the productive conflict presented by the theoretic foundation of the culture of peace. However, although the teachers understand about this issue, it is not clearly characterized that the dialogic work com the community is one of its attributions. In order to engender this kind of culture, it is necessary to see the close relationship between the AEE pedagogical work and the humanizing policy in the dialogical education context with the school community.